Morphological effects of mechanical forces on the human humerus. Issue 1 (March 1992) - Qu, X
Abstract : Various mechanical forces produce a variable stimulus intensity on bone and have different effects on its growth and development. The aim of this project was to study the effects of a variety of mechanical forces on human humerus morphology. This was investigated by measuring the cortical thickness (cm) and diameter (cm) of the humerus at its proximal, middle and distal thirds from radiographs. The humerus of each of 46 men (five controls, six swimmers, eight gymnasts, seven javelin throwers, nine discus throwers and 11 weightlifters) was radiographed on both right and left sides. The humerus size variation among the participants, in order of increasing size, was found to be as follows: gymnasts, controls, swimmers, javelin throwers, weightlifters and discus throwers respectively. The humeral cortex was largest in the weightlifters, being significantly (P less than 0.05) thicker at distal, medial and proximal sites. The proximal and distal humeral sites in javelin and discus throwers were significantly thicker than those of the control subjects. From the results, static load would seem to provide a higher stimulus to bone than dynamic loading.